CORALS AS SOURCE OF BACTERIA WITH ANTIMICROBIAL ACTIVITY - ocky radjasa; Jutta Wiese; Agus Sabdono; Johannes F Imhoff (JOURNAL OF COASTAL DEVELOPMENT, 2008)
In this study we examined marine bacteria associated with different corals (Porites lutea, Galaxea fascicularis, Acropora sp. and Pavona sp.) collected from vicinity of Panjang island, Jepara, North Java Sea, Indonesia for their antimicrobial activities against the bacteria Echerichia coli, Bacillus subtilis, Staphylococcus lentus and the yeast Candida glabrata. A total of 13 bacterial isolates belonged to the members of Bacillus, Vibrio, Micrococcus, Pseudoalteromonas, Arthrobacter and Pseudovibrio were found to inhibit the growth of at least one test strain. Further examinations among the biologically active strains by using PCR with specific primers of non-ribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) resulted in the presence of NRPS gene fragments in the 2 members of Bacillus and Micrococcus and PKS gene fragments in the 2 members of Bacillus and Vibrio. Following cloning and sequencing of the PCR products, the fragments from Bacillus BM1.5 and Micrococcus BJB showed sequence identity with peptide synthetase genes of Bacillus subtilis (61 %) and Actinoplanes teichomyceticus (62.4%). On the other hand, PKS-amplifying strains Bacillus BJ.7 and Vibrio MJ.5 showed closest sequence identity with polyketide synthase genes of Bacillus subtilis (73%) and Anabaena sp 90 (62%), respectively.